ANALYSIS OF THE TYPES AND CHARACTERISTICS OF THE TIDES USING THE ADMIRALTY METHOD ON TWO RIVERS IN THE KUBU RAYA DISTRICT - Nirmala, Azwa; Hafiyyan, Qalbi (Fakultas Teknik Universitas Tanjungpura, 2023)
A study of the tides in the river has been carried out in this paper. The rivers studied are the Jawi River (Kakap) and the Nipah River. The two rivers are located in Kubu Raya Regency, West Kalimantan. This study aims to determine the type of tides and water level elevation in the two rivers. This study uses the Admiralty method to analyze existing tidal data. This method is commonly used in tide analysis. The results show that the tidal type of the Jawi River is a diurnal tide. The water level in the Jawi River is HHWL of 1.4 m (+0.86 m from MSL) and LLWL of